Patient with Pneumomediastinum and Air in the Spine - Amidi, F; Tafti, SF; Talischi, F; Kahkouee, S; Cheraghvandi, A; Montazeri, P (Bangladesh Journal of Medical Science, 2013)
Air in the epidural space of the spine in most cases is found in association with air in other body locations including pneumothorax, pneumomediastinum, pneumopercardium and subcutaneous emphysema. Most spontaneous cases resolve on their own. Here we present a 3 year old boy with pneumomediastinum and pneumorrhachis that resolved with supportive care. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16670 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 456-458